The direct option - Bartlett, Dick, 1935- (Texas A & M University Press, 1994)
Party plans, individual calls, customer lists - this hands-on guide to a career in direct selling introduces readers to one of the fastest-growing sectors of the American economy. Companies such as Avon, Mary Kay, Shaklee, Amway, and Discovery Toys offer careers - part- or full-time - to millions of Americans, nine out of ten of whom are women. The beauty of direct selling is the ease of entry: low cost, no educational requirements, no age, ethnic, disability, or other barrier to achieving success.